2019
DOI: 10.1111/ppc.12389
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the eye movement desensitization and reprocessing intervention on anxiety and depression among patients undergoing hemodialysis: A randomized controlled trial

Abstract: Purpose This study examined the effect of the eye movement desensitization and reprocessing intervention on depression and anxiety in patients undergoing hemodialysis. Design and Methods In this randomized controlled trial, 90 patients were enrolled. The intervention group received six sessions of the eye movement desensitization and reprocessing intervention. Data were collected before and 2 weeks after the intervention using the Hospital Anxiety and Depression Scale. Findings Measured levels of anxiety and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Similar positive results were found in three RCTs that reported a decrease in anxiety and depression scores in, patients requiring haemodialysis treatment (Rahimi et al, 2019 ), and in patients suffering from spinal cord injury (Hatefi et al, 2019 ). In the same vein, a group study (Zolghadr et al, 2019 ) found a decrease of anxiety scores in one single session of EMDR in a group of pregnant women with a history of stillbirth compared to a control group.…”
Section: Resultssupporting
confidence: 73%
“…Similar positive results were found in three RCTs that reported a decrease in anxiety and depression scores in, patients requiring haemodialysis treatment (Rahimi et al, 2019 ), and in patients suffering from spinal cord injury (Hatefi et al, 2019 ). In the same vein, a group study (Zolghadr et al, 2019 ) found a decrease of anxiety scores in one single session of EMDR in a group of pregnant women with a history of stillbirth compared to a control group.…”
Section: Resultssupporting
confidence: 73%
“…The positive treatment effect on anxiety and depression symptoms is in line with results of EMDR treatment for anxiety in glioblastoma multiforme patients, 21 and patients undergoing hemodialyses. 22 Presumptive evidence of a decrease of worrying thoughts after EMDR therapy has also been found in three female patients with generalised anxiety disorder. 35 The most important limitations of this study are the sample size and the lack of a control group.…”
Section: Discussionmentioning
confidence: 91%
“…21 Also there was a positive treatment effect of the EMDR intervention on anxiety and depression levels among patients undergoing hemodialysis. 22 Despite the value of these findings, no research has been found on EMDR specifically focused on anxiety related to the future in other medical diseases like MS.…”
Section: Eye Movement Desensitization Reprocessing Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…2 According to estimates, nearly one million patients are undergoing dialysis treatment and it has been predicted that this number will increase up to 5.5 million by 2030. 5,6 Department of Nephrology, Shrimann Superspeciality Hospital, Pathankot Road, Jalandhar, Punjab, India Dialysis treatment is considered to be a long-term treatment and it leads to significant physical and psychological side effects. The stress, anxiety, and depression are the usually reported psychosomatic concerns in patients on hemodialysis.…”
Section: Introductionmentioning
confidence: 99%